SURVEY MENGENAI EMPLOYEE ENGAGEMENT, KEPUASAN KERJA, KOMITMEN DAN TURNOVER INTENSION PADA KARYAWAN RUMAH SAKIT AVICENA BIREUEN - Syamsul Asuro (Universitas Islam Islam Sumatera Utara, 2018)
This study aims to determine how the conditions or job attitude of the employees of Avicena Bireuen Hospital. This is based on the dilemma of information between job satisfaction and the desire to leave work among the hospital employees. This study uses a survey approach where data is obtained by distributing structured questions with available answer choices. In addition, questionnaires were distributed to 40 respondents as research samples. Data were analyzed using tabulations, scorring and percentages. The results show that work facilities are in good condition, the company consistently gives the rights of its employees on time. In working relationships in the company there is warmth that occurs between co-workers, harmoniously. Before working, prospective workers were also given training according to their respective fields of work. In terms of ideas and suggestions, all company employees respond each others proportional appreciation. Hence, the company's payroll system can be said according to the duties and a position of its employees, even the company also provides benefits beyond the basic salary. Coordination between parts or sections is also well connected so that good work relationships are built between employees.